Native versus alien status of a rare plant species outside the limits of its main geographic range: distribution of Virga pilosa (L.) Hill in Wielkopolska, Poland and CE Europe - Stachnowicz, Wojciech; Rakowski, Wojciech (Biodiversity: Research and Conservation, 2013)
Virga pilosa (L.) Hill (= Dipsacus pilosus L.) is an example of a phytogeographically controversial species. Being nationally rare (in Poland), it sometimes becomes locally frequent and maybe even expansive. Its native vs alien status remains disputable, at least in a regional scale. This article provides a new, cartographical and phytocoenological documentation of the species occurrence within a forest complex situated in the middle part of the Wielkopolska region, Poland. It also contains new, updated distribution maps of Virga pilosa in Poland and Central Europe. The authors discuss the species‘ phytocoenological scale, particularly, in order to find potential explanations of its abundant presence within a single, in a supra-regional scale, and spatially separated locality. They conclude in relation to the species alien status in the region of Wielkopolska, where Virga pilosa has been recently established in one locality, that it is locally naturalised and spreading.